ANALISIS HIGHEST AND BEST USE PEMANFAATAN TANAH KOSONG DI KELURAHAN PENKASE OELETA KOTA KUPANG - Henuk, Wulan Elisabeth; Tameno, Nikson; Tungga, Cicilia Apriliana (LPPM University 17 Agustus 1945 Samarinda, 2023)
This study discusses and implements the Highest and Best Use (HBU) Analysis method for fixed assets under the management and ownership of the Kupang City Government in the form of unused vacant land, located in Penkase Oeleta Village, Alak District, Kupang City, East Nusa Tenggara Province. This type of research is a quantitative descriptive research. Data collection techniques were carried out using questionnaires, interviews, observation and documentation. This study uses the Highest and Best Use analysis to determine the most optimal type of utilization of the research object's land for four aspects which include physical aspects, legal aspects, financial aspects and maximum productivity. The results of the study show that the Highest and Best Use Analysis in terms of the physical aspect of alternative land uses as Public Warehouses, Grocery Warehouses and as Housing is possible to do, while based on legal aspects, alternative land uses as Public Warehouses and Grocery Warehouses are permitted, while use as Housing is not permitted, then based on the financial aspect of the alternative land use as a Public Warehouse meets the eligibility criteria, namely an NPV of Rp. 2,194,024,971., IRR is 18% and the highest land value is Rp. 5,398,430,092. The basic food warehouse meets the eligibility criteria, namely an NPV of Rp. 3,072,079,311., IRR is 25% and the highest land value is Rp. 9,553,342,631,. The results of the analysis show that the highest and best land value is an alternative use as a Grocery Warehouse, which is Rp. 8,741,064 per square meter or an increase in land value by 4% compared to the market value of vacant land for the research object, which is Rp. 1,993,029., per square meter. So the highest and best utilization of vacant land is the Grocery Warehouse.